2019
DOI: 10.51804/jsh.v3i1.336.21-29
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor Kejadian Phlebitis Dengan Simulasi Model Fisis Alat Terapi Intravena

Abstract: Intravenous therapy through long-term infusion is at risk for complications such as phlebitis. The influence of medical factors with a history of hypertension and mechanical factors based on the location of the position of infusion is the main study of the causes of phlebitis.One of the causes of phlebitis is the flow of intravenous fluids which is not proportional to the volume of infusion fluid. Intravenous Therapy Devices with the aim of assessing the physical phenomena modeling experiments intravenous ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The WHO (2017) reported that there are 10 global public health facts about nosocomial infections, including those are phlebitis which is a serious problem, found 1 in 300 patients likely injured during treatment in health care, especially in hospitals [2], [4], [5] and about 6.2% infections due to intravenous therapy [6]. The incidence rate of phlebitis in Southeast Asia annually reaches 10%, data from the CDC (2017) indicate that the incidence of phlebitis ranks fourth as an infection often found in patients during hospital treatment.The figures of the highest phlebitis in developing countries were: India (27.91%), Iran (14.20%), Malaysia (12.70%), Philippine (10.10%) and Indonesia (9.8%) [7].…”
Section: Introductionmentioning
confidence: 99%
“…The WHO (2017) reported that there are 10 global public health facts about nosocomial infections, including those are phlebitis which is a serious problem, found 1 in 300 patients likely injured during treatment in health care, especially in hospitals [2], [4], [5] and about 6.2% infections due to intravenous therapy [6]. The incidence rate of phlebitis in Southeast Asia annually reaches 10%, data from the CDC (2017) indicate that the incidence of phlebitis ranks fourth as an infection often found in patients during hospital treatment.The figures of the highest phlebitis in developing countries were: India (27.91%), Iran (14.20%), Malaysia (12.70%), Philippine (10.10%) and Indonesia (9.8%) [7].…”
Section: Introductionmentioning
confidence: 99%